2012
DOI: 10.1016/j.diabres.2011.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Islet autoantibodies and residual beta cell function in type 1 diabetes children followed for 3–6 years

Abstract: Islet autoantibodies and residual beta cell function in type 1 diabetes children followed for 3-6 years Sorensen, J. S.; Vaziri Sani, Fariba; Maziarz, M.; Kristensen, K.; Ellerman, A.; Breslow, N.; Lernmark, Åke; Pociot, F.; Brorsson, C.; Birkebaek, N. H.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…Moreover, individuals with negative tests for ZnT8A represented a sizable proportion of those with two or more autoantibodies (118 of 237 [50%]). Reports describing T1D patients in the years after diagnosis suggest that ZnT8A autoantibodies are important to understanding pathogenesis (2729). The particular significance of ZnT8A autoantibodies shows why specific types and levels of autoantibodies should be considered to avoid faulty determinations of eligibility for prevention trials.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, individuals with negative tests for ZnT8A represented a sizable proportion of those with two or more autoantibodies (118 of 237 [50%]). Reports describing T1D patients in the years after diagnosis suggest that ZnT8A autoantibodies are important to understanding pathogenesis (2729). The particular significance of ZnT8A autoantibodies shows why specific types and levels of autoantibodies should be considered to avoid faulty determinations of eligibility for prevention trials.…”
Section: Discussionmentioning
confidence: 99%
“…The study group included 342 children and adolescents, of whom 97% were positive for one or more diabetes-specific autoantibodies at diabetes onset (29). Great diversity concerning RBF phenotype was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated C-peptide level equal to or just higher than our lower detection limit may not affect the clinical outcome but may serve as an autoantigen stimulus (29). Schiffrin et al (19) found that 23% of 151 Canadian children and adolescents with type 1 diabetes onset during 1985–1988 had stimulated C-peptide >0.06 nmol/L at 3 years after diabetes onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been reported that the predominant factor associated with a rapid loss of RBF is young age . The causal effect of autoantibodies on RBF has remained unclear because of conflicting results . Human leukocyte antigen (HLA) genotype, a history of diabetic ketoacidosis (DKA) at diagnosis, C‐peptide levels at diagnosis, sex, and body mass index (BMI) are also factors that affect RBF after diagnosis in adolescents and young adults …”
Section: Introductionmentioning
confidence: 99%